“Into the Thick of the Fray” - Burlingham, Kate (Social sciences and missions, 2015)
This article considers American foreign relations with Angola by exploring the application of so-called adaptive education. Beginning in 1919, black American missionaries at the Congregational Galangue mission station instituted systems of schooling originally developed among freedmen and women in the American South after the Civil War. These pedagogies were specifically designed to educate black Americans without upsetting dominant white structures. When transferred to Angola, these same teachings helped to empower Angolans economically and, ultimately, politically. And yet, they carried with them the unresolved legacy of American slavery. The success of Southern-inspired mission schools among Angolans opens up new questions about the legacies of slavery in US foreign relations with Angola and Africa.